An Open Label Comparative Clinical Study on the Effectiveness of Homoeopathic Medicines Vis-À-Vis Bach Flower Remedies in Depressive Disorders (Advancements in Homeopathic Research, 2022)
Background: Depression is a common and often under-diagnosed mental disorder. Besides homoeopathic medicines, Bach flower remedies are also recommended by the practitioners for psychological problems, including depression. Objective: To compare the role of homoeopathic medicines and Bach flower remedies in depressive disorders on the basis of pre- and post- treatment scores on Hamilton Depression Rating Scale. Material and Methods: A randomized, open label clinical study was carried out from May 2016 to April 2017. In this study, cases with Major depressive disorder and Persistent depressive disorder presenting with mild to moderate depression were included. Homoeopathic medicines were prescribed on the basis of Hahnemannian guidelines whereas Bach flower remedies were prescribed as per guidelines of Dr. E. Bach. Outcome was assessed by using the Hamilton depression rating scale. Results: Data of 70 patients (26 males and 44 females) enrolled in the study were analyzed. Independent t test (mean difference= 3.057; standard error of means= 0.636; p = 0.00) showed that homoeopathic medicines were more effective than Bach flower remedies in cases of depressive disorders. The most frequently used homoeopathic medicine was Natrum muriaticum (n=10). The most frequently used Bach flower remedy was Star of Bethlehem (n=9). Conclusion: It is concluded that homoeopathic medicines are more effective than Bach flower remedies in cases of depressive disorders.
Keywords: Depressive disorder; Homoeopathic medicines; Bach flower remedies; Hamilton Depression Rating Scale (HDRS)